THE USE OF LEARNING VIDEO MEDIA TO INCREASE STUDENT LEARNING INTEREST IN BIOLOGY SCIENCE LESSONS AT SMP NEGERI 3 MERBAU - Lusiana; Minah; Erlia Utami Panjaitan; Syahraini Ritonga (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Low student interest in learning is a common problem that occurs in schools. The problem of low student interest in learning also occurs in SMP Negeri 3 Merbau in Biology Science learning,especially in Cell material. The main cause oflowstudent interest in learning is because students cannot see the shape of the cell structure directly so that they find it difficult to understand the abstract conceptsof cell material. This study uses a descriptive method, describing the state of a research object with facts that appear to be true. The data collection techniqueused in this study was direct interviews with research instruments in the form of interview sheets. Other factors that cause low student interest in learning Biology Science learning are the difficulty of students to focus during learning, low student memory skills, and lack of tools for the learning process. The use of video as a learning medium is a solution to solve the problems that occur. This is because videolearningmediaprovidesmanybenefitstobothstudentsandteachers, namely video teaching media increases student interest in learning, students are enthusiastic in listening to the material presented. With learning using videos, students can remember the material longer and their curiosity also increases.